Water condensation system based on thermoelectric coller using solar energy - A.N. Abirami; C.R. Balamurugan; D. Meena (International Journal of Advances in Applied Sciences, 2020)
The main objective of the paper is to develop a water condensation system based on thermoelectric cooler using solar Energy to convert atmospheric moisture directly into usable and even drinking water. This idea can be extended further in future – For large scale implementation, RO and UV water filter can be used for producing such water that meets the standard of WHO and BIS easily. Peltier device has many types of models which are much efficient than TEC1. Those can be used. As the paper aims at producing water from atmosphere and keeping this device handy, large sized scrubbers are not used for better air filtration. Scrubbers can remove all the oxides from the air. For large implementation it can be handled. The concept of this paper can also be used as a better alternative in refrigeration science against conventional systems. It can also be observed in this way i.e. the usage of such low power semiconductor devices are indicating towards more prominent evolution of cooling engineering that is going to alter the whole scenario and myths about the power consumption of refrigeration science. Thus in near future we will be able to use such devices that are now limited within the paper.